Overproduction of microbial products--facts and ideas - Vanek, Z; Hostálek, Z; Spízek, J (Biotechnology advances, 1990)
Overproduction of microbial metabolites is related to developmental phases of microorganisms. Inducers, effectors, inhibitors and various signal molecules play a role in different types of overproduction. Primary and secondary metabolism are interconnected. Biosynthesis of enzymes catalyzing metabolic reactions in microbial cells is controlled by well-known positive and negative mechanisms, e.g. induction, repression, catabolite repression, mechanisms controlling enzyme activity include isosteric and allosteric interactions, e.g. competitive and non-competitive inhibition, allosteric effects, molecular conversion etc. Biosynthesis of secondary metabolites is catalyzed by unaltered enzymes of primary metabolism, by altered enzymes of primary metabolism and by specific enzymes of secondary metabolism. In addition to classical mutagenesis and selection of suitable microbial cells, methods of molecular genetics are used in the overproduction of microbial products.